Planning for Economic Development the Indian Experiment A Series of Five Articles by Pitambar Pant A Vaidyanathan - Planning Commission (Planning Commission, 1965)
During the last twenty years since the end of the World War II, a remarkable change has come about in the world. Many countries which had been under the YOKO of imperialism have regained their freedom. A new awakening has come that poverty and ignorance and disease are not inevitable and can be wiped away from the face of the earth by purposeful effort. The accumulated store of knowledge and techniques and the continuing advance in science and technology provides the basis for a rapid transformation of the material conditions. The valuable experience of many countries in evolving political and economic organizations required to deal with such problems and an atmosphere of international cooperation have made the task easier.
Planning Commission
Planning Commission